Evaluation of durability of stabilized soft soils under changing weather conditions - Hamid Reza Akbari; Azam Entezari Harsini (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
Soil amendment methods have made significant progress in terms of economics and compatibility with the environment, so that currently the focus is on long-term evaluations of these methods. The many benefits of stabilization have made this method to be considered as the target plan in many soft soil improvement researches. Stabilized soils are always under weather conditions, so evaluating the long-term durability of stabilized soils can be important in choosing a method. For this purpose, kaolinite soil stabilized with lime and reinforced with polypropylene fibers was subjected to wet-dry and freeze-thaw cycles, and the mechanical behavior of the samples was analyzed by conducting compressive strength and indirect tensile strength tests.The results show that the wet-dry cycle is clearly more destructive than the freeze-thaw cycle and the use of the stabilization plan including 12% lime along with 1.25% polypropylene fibers has a good performance against the cycles of weather conditions and maintains 76% of its strength and provides the minimum strength required for the sub-base.